Cystoid macular oedema in paediatric aphakia and pseudophakia. Issue 1 (16th December 2005) - Kirwan, C; O'Keeffe, M
Abstract : Aim: To assess the incidence of cystoid macular oedema (CMO), following lensectomy, anterior vitrectomy (limbal and pars plicata), and primary posterior capsulorhexis following surgery for congenital and developmental cataract. Methods: A prospective study was carried out involving 30 eyes (20 children) with cataract. Lensectomy, primary posterior capsulorhexis, and anterior vitrectomy were performed on all eyes. Vitrectomy was performed using either a limbal or pars plicata approach. Fluorescein angiography was carried out 4–7 weeks after surgery. Fluorescein was administered intravenously and visualised using the Retcam. Results: Anterior vitrectomy was carried out via the limbal approach in 12 eyes and, of these, six were implanted with an intraocular lens. The pars plicata approach was carried out in 18 eyes and 10 received an implant. CMO was not detected in any eye. Conclusion: CMO was not detected in the early postoperative period irrespective of approach to anterior vitrectomy or presence of an intraocular lens. Intravenous fluorescein angiography was performed without complication